Effects of wheat and corn gluten on growth performance, histopathologic and autoimmune metabolism of entero-hepatictissue in lambs - Can, MB; İmik, H and Terim Kapakin, KA (Journal of the Hellenic Veterinary Medical Society, 2024)
This study investigated the effects of wheat gluten and corn gluten, alone as a protein source into rations as protein sources, on fattening performance and the histopathological and autoimmune metabolism of the small intestinal and hepatic tissues in lambs. The animals enrolled in the study were fed on isonitrogenous and isoenergetic diets. The protein sources provided to the animals were soybean meal and safflower meal in the control group, wheat gluten in Group Wheat, and corn gluten in Group Corn. The study animals included 24 male Morkaraman (Red Karaman) lambs, which were of a mean age of 9 months and assigned to three groups, each of 8 animals. Mean daily body weight gain (0-56 day) were observed to be significantly lower in Group Wheat (p<0.05). Mean daily feed intake were observed to be significantly lower in Group Wheat and Group Corn (p<0.05). At the end of the study, when compared to the control group, Group Wheat displayed significantly higher levels of villous atrophy, inflammation, crypt hyperplasia and transglutaminase immunopositivity in the small intestinal tissue as well as necrosis, inflammation, bile duct hyperplasia and transglutaminase immunopositivity in the hepatic tissue, and a lower level of degeneration in the liver (p<0.05). The findings detected in Group Corn were variable. In result, wheat gluten significantly affected both performance parameters and the histopathological and autoimmune metabolism of the intestinal and hepatic tissues in lambs. Key words: Corn; gluten; lamb; wheat; histopathological